ROLE OF ULTRASOUND GUIDED FINE NEEDLE ASPIRATION CYTOLOGY IN DIAGNOSIS OF SPACE OCCUPYING LESIONS OF LIVER - Sattar, Abdul; Khan, Abdul Majeed; Anjum, Sadia; Naqvi, Abbas (Journal of Ayub Medical College Abbottabad, 2014)
Background: Ultrasound guided fine needle aspiration cytology (FNAC) is a valuable technique for diagnosing benign and malignant space occupying masses of liver. It is a cost effective and safe method that can differentiate benign and malignant lesions accurately. The objective of this study was to analyse cases of radiologically guided fine needle aspiration cytology of space occupying lesions of liver. Methods: Ultrasound guided FNAC of liver masses was carried out on 450 admitted patients with focal lesions liver on ultrasound. Patients of all ages and both sexes were included. The study was conducted in department of Diagnostic radiology in collaboration with the Pathology Department at Nishtar Medical College & Hospital, Multan over a period of two years from August, 2009 to August, 2011. The aspirates were done by senior radiologist in Radiology Department. Results: Most of the aspirates were from males. Ten cases were considered inadequate. There were more malignant cases (320 cases) as compared to benign lesions (120 cases). Metastatic lesions were more common as compared to hepatocellular carcinoma (HCC); however the ratio of metastatic adenocarcinoma and primary HCC was almost equal. Conclusion: Ultrasound guided FNAC is a simple, quick and complication free procedure for diagnosing space occupying lesions of liver. Keywords: FNAC, HCC, Histopathology, liver, metastasis